2016
DOI: 10.4314/ahs.v16i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early skin-to-skin contact on the rate of exclusive breastfeeding in term neonates: A randomized controlled trial

Abstract: Background: Despite multiple benefits of breast milk, the rates of exclusive breastfeeding in developing countries are low. Objective: To evaluate the efficacy of early skin -to -skin contact (SSC) on the rate of exclusive breastfeeding (EBF) at 6 weeks of age among term neonates born by vaginal delivery. Methods: Term neonates born by vaginal delivery and did not require any resuscitation were randomized at birth to SSC (n=100) and control (n=100) group. Immediately after clamping the umbilical cord, SSC grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 22 publications
7
51
0
18
Order By: Relevance
“…The associations were significant among infants at discharge (74.5% vs. 55.0%), 3 months (OR=3.20), and 6 months (OR=4.91) of age. Our findings were consistent with previous researches, which showed that infants provided with SSC were more likely to be breastfed at hospital discharge [33], day 28 [32], 1 month [29], and 6 weeks after birth [36]. A review by Moore et al in 2016 of 38 trials with 3472 pairs covering 21 countries found that women who received SSC were more likely to exclusively breastfeed their babies from 6 weeks to 6 months (RR: 1.50; 95% CI: 1.18, 1.90) of age [37].…”
Section: Discussionsupporting
confidence: 93%
“…The associations were significant among infants at discharge (74.5% vs. 55.0%), 3 months (OR=3.20), and 6 months (OR=4.91) of age. Our findings were consistent with previous researches, which showed that infants provided with SSC were more likely to be breastfed at hospital discharge [33], day 28 [32], 1 month [29], and 6 weeks after birth [36]. A review by Moore et al in 2016 of 38 trials with 3472 pairs covering 21 countries found that women who received SSC were more likely to exclusively breastfeed their babies from 6 weeks to 6 months (RR: 1.50; 95% CI: 1.18, 1.90) of age [37].…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, according to the results of the present study, the postnatal skin contact of the mother and neonate could increase the exclusive breastfeeding rate. It is suggested that contact between the mother and baby be adopted as a care method by maternal and child health care providers, such as midwives, doctors, and students responsible in childbirth (34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Research continued to document the benefits of KC on breastfeeding rates and exclusivity of breastfeeding (Gathwala et al, 2010;Keshavarz & Haghighi, 2010;Srivastava et al, 2014). Sharma (2016) reported a significantly higher proportion of full-term infants who received early KC (72%) were exclusively breastfeed at 6 weeks of age than infants who did not get KC.…”
Section: -2019-kc Research Continues While Adding New Themesmentioning
confidence: 99%